1994
DOI: 10.1007/bf00365731
|View full text |Cite
|
Sign up to set email alerts
|

Complications of spinal opioid therapy: myoclonus, spastic muscle tone and spinal jerking

Abstract: This study was made in order to define risk factors for patients requiring spinal opioid therapy developing painful spastic muscle tone together with myoclonus and spinal jerking (MSJ). The case histories of 75 patients, all receiving morphine spinally, were retrospectively analysed and, of these, 10 suffered from the MSJ syndrome. The following were taken as evaluation criteria: age, sex, performance status, duration and dosage of previous systemic and current spinal morphine therapy, concomitant analgesic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 15 publications
0
18
0
2
Order By: Relevance
“…[9,11,12] Özellikle spinal kord veya nöromüsküler disfonksiyonu olanların risk altında olduğu belirtilmektedir. Dozdan bağımsız olarak opioid ile ilişkili spinal miyoklonus olguları bildirilmiş olmakla birlikte, daha çok yüksek opioid dozunun spinal ve santral opioid reseptörlerinin aktivitelerinde dengesizlik yaratarak miyoklonusa neden olduğu ifade edilmektedir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…[9,11,12] Özellikle spinal kord veya nöromüsküler disfonksiyonu olanların risk altında olduğu belirtilmektedir. Dozdan bağımsız olarak opioid ile ilişkili spinal miyoklonus olguları bildirilmiş olmakla birlikte, daha çok yüksek opioid dozunun spinal ve santral opioid reseptörlerinin aktivitelerinde dengesizlik yaratarak miyoklonusa neden olduğu ifade edilmektedir.…”
Section: Discussionunclassified
“…Dozdan bağımsız olarak opioid ile ilişkili spinal miyoklonus olguları bildirilmiş olmakla birlikte, daha çok yüksek opioid dozunun spinal ve santral opioid reseptörlerinin aktivitelerinde dengesizlik yaratarak miyoklonusa neden olduğu ifade edilmektedir. [11] Bizde olgumuzda kullandığımız fentanil infüzyonu sırasında dozun oldukça düşük olması nedeniyle myoklonik aktive gözlemlemediğimizi düşünmekteyiz.…”
Section: Discussionunclassified
“…Hyperalgesia and myoclonus have been described in patients being given high intraspinal doses of morphine, probably due to a disinhibition of glycinergic and GABAergic control systems by morphine or its metabolites at the spinal cord [13,47]. High spinal morphine doses in conjunction with pathological changes within the spine were shown to be risk factors for myoclonus and spinal jerk syndrome [33]. It has been suggested that during intrathecal infusion morphine gets trapped below a spinal block provoked by tumour growth, giving rise to local toxic CSF concentration of morphine provoking seizure-like muscular contractions of the lower limbs [10].…”
Section: Adverse Effects Of Spinal Opioidsmentioning
confidence: 97%
“…It has been suggested that during intrathecal infusion morphine gets trapped below a spinal block provoked by tumour growth, giving rise to local toxic CSF concentration of morphine provoking seizure-like muscular contractions of the lower limbs [10]. An imbalance between the activity of spinal and central opioid receptors and toxic morphine effects on the spinal cord have been reported as possible underlying mechanisms [33]. Since patients develop paresis and paralysis of their extremities, some authors have speculated that myoclonic-like spasms might be secondary to intraspinal spread of malignancy [35].…”
Section: Adverse Effects Of Spinal Opioidsmentioning
confidence: 99%
“…To evaluate this object, patients' histories were evaluted in several retrospective studies, each including about 100 patients [4][5][6][7][8]. In summary, nearly all patients (except 2%) obtained adequate pain control.…”
Section: Treatment Modalitiesmentioning
confidence: 99%